New genus, species, redescription, and new rank in Cerambycinae (Coleoptera, Cerambycidae) - Vlasak, Josef; Santos-Silva, Antonio (Zootaxa, 2018)
Two new species of Cerambycidae are described from Costa Rica: Cosmisoma luteoviridis sp. nov. (Rhopalophorini) and Katerinaella costaricensis gen. nov. and sp. nov. (Rhinotragini). Trachyderes (Dendrobias) Dupont, 1834 is restored to genus level. Male specimens of Dendrobias steinhauseni (Hüdepohl, 1987) from Nicaragua and Costa Rica are described and illustrated. The relationship of D. steinhauseni with other Dendrobias species is discussed.